FAKTOR-FAKTOR YANG MEMPENGARUHI CADANGAN DEVISA INDONESIA - Raif Bagaskoro Resdianto (2021)
One of the economic problems faced by Indonesia is the level of availability of its foreign exchange reserves. This study aims to determine the effect of exports, imports, inflation, exchange rates and gold prices on Indonesia's foreign exchange reserves. Determination of the sample using a saturated sampling technique with all 5 variables from 1989 to 2019 so that the total sample is 31. The data used is secondary data obtained from the Central Statistics Agency, the World Bank and investing.com. This study uses multiple linear regression analysis techniques and the tools used to analyze this study using Eviews 10 and Microsoft Excel with a significance level of 5% (0.05). The results of the study partially show that (1) exports have a significant effect on Indonesia's foreign exchange reserves (2) imports have no effect on Indonesia's foreign exchange reserves (3) inflation has a significant effect on Indonesia's foreign exchange reserves (4) the exchange rate has a significant effect on Indonesia's foreign exchange reserves and (5 ) the price of gold has no effect on Indonesia's foreign exchange reserves.